2021
DOI: 10.1093/sysbio/syab100
|View full text |Cite
|
Sign up to set email alerts
|

Robust Analysis of Phylogenetic Tree Space

Abstract: Phylogenetic analyses often produce large numbers of trees. Mapping trees’ distribution in ‘tree space’ can illuminate the behaviour and performance of search strategies, reveal distinct clusters of optimal trees, and expose differences between different data sources or phylogenetic methods – but the high-dimensional spaces defined by metric distances are necessarily distorted when represented in fewer dimensions. Here, I explore the consequences of this transformation in phylogenetic search results from 128 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…The existence of rogues militates for a detailed evaluation of optimal trees. The only way to fully evaluate the signal within a set of trees is to scrutinize each individual topology, perhaps assisted by an exploration of the underlying tree space ( St. John 2017 ; Smith 2022 ) and the construction of a “profile” of complementary consensus trees ( Wilkinson 1996 ; Wilkinson 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of rogues militates for a detailed evaluation of optimal trees. The only way to fully evaluate the signal within a set of trees is to scrutinize each individual topology, perhaps assisted by an exploration of the underlying tree space ( St. John 2017 ; Smith 2022 ) and the construction of a “profile” of complementary consensus trees ( Wilkinson 1996 ; Wilkinson 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…A subsample of the individual bifurcating trees reconstructed by each approach was compared by mapping the clustering information and quartet distances [109,110] between each pair of trees into two dimensions using classical multidimensional scaling [111], using the R packages 'QUARTET' and 'TREEDIST' [112,113]. Adequacy of projection was indicated by trustworthiness and continuity metrics above 0.90 and minimal deformation of the minimum spanning tree [114][115][116][117]. This analysis indicated that all methods except uncorrected Fitch parsimony converged onto a similar region of tree space.…”
Section: Methodsmentioning
confidence: 99%
“…treespace (Jombart et al 2017) is an R package that allows a wide variety of tree metrics and methods for clustering trees to be used. Smith (2022) evaluated the performance of multiple aspects of low-dimensional representations of sets of trees, and provides an R package TreeDist for users to do the same. Finally, R We There Yet (RWTY) (Warren et al 2017), a package for analyzing Bayesian analyses convergence, can produce nonlinear MDS visualization of landscapes using the RF or path difference distance (Steel and Penny 1993) and colored by the likelihood.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, R We There Yet (RWTY) (Warren et al 2017), a package for analyzing Bayesian analyses convergence, can produce nonlinear MDS visualization of landscapes using the RF or path difference distance (Steel and Penny 1993) and colored by the likelihood. Some authors (Amenta et al 2015; Wilgenbusch et al 2017; Smith 2022) have analyzed how well MDS visualizes treespace, and suggested validation measures. There are other ways to visualize sets of related trees beyond dimensionality reduction, such as super-imposing the trees on each other, as in DensiTree (Bouckaert 2010), or sophisticated tree comparison visualizers, like ADView (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation